Utilization of coconut residue in cinnamon rolls - Santos, Glycerio Bravo; Galvez, Flor Crisanta F. (1995.)
Coconut residue flour (CRF) was utilized in the production of cinnamon rolls as a substitute for all purpose flour. The procedure for making cinnamon rolls with coconut residue flour was standardized according to acceptability of the final bread. Only basic ingredients for bread making were used and as the level of substitution increased the water to be added deceased. The effects of 0, 10, 20, 30, 40, and 50% substitution moisture, protein, fat, and crude fiber and on consumer acceptability of cinnamon rolls were determined. Acceptability of the product to the consumers were determined using a 9-point hedonic scale where 1=dislike extremely, 5= neither like nor dislike, and 9=like extremely. Results showed that increased substitution of all purpose flour with CRF increased the crude protein, crude fiber and moisture content of all the cinnamon rolls. Products with 50% CRF substituted with all purpose flour were found most acceptable to consumers.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Coconut residue flour